Analyzing the effects of Spiritual Intelligence, Innovation and Competence on Employee Appearance at PT. Asam Jawa - Serly Fimasari; Iskandarini Iskandarini; Dewi Kurniawati (RIRAI Publisher, 2024)
The research is conducted at PT. Asam Jawa in Medan, North Sumatra, from September to October 2023. The research population comprises all employees of PT. Asam Jawa, totaling 50 individuals, and the sampling is done exhaustively involving all population members. From the research results and discussions, the following conclusions can be drawn: (1) Spiritual Intelligence has a positive and significant influence on the improvement of Employee Appearance at PT. Asam Jawa. (2) Innovation has a positive and significant influence on the improvement of Employee Appearance at PT. Asam Jawa. (3) Competence has a positive and significant influence on the improvement of Employee Appearance at PT. Asam Jawa. (4) Spiritual Intelligence, Innovation, and Competence have a positive and significant influence on the improvement of Employee Appearance at PT. Asam Jawa. Recommendations for the company involve engaging in the development of spiritual intelligence, fostering an innovative culture, and focusing on the development of employee competence. The research results can serve as a reference for companies to understand the impact of these factors on appearance improvement. For future research, it is suggested to include additional variables such as leadership, job stress, organizational behavior, and other management variables.